Combining efficiency with ROA: indicator of future relative performance - South African banking groups - Cronje, Tom; Beer, J. (Virtus Interpress, 2010)
Bank financial performance and relative future financial performance are important issues to stakeholders like management, shareholders, investment analysts and portfolio managers. This paper provides evidence that bank financial performance expressed as return on assets (ROA) figures that are adjusted according to relative income and expenditure efficiency provide fundamental measures of performance that have a causal link with future profits and can be utilised in estimating future financial performance. The methodology applied in this research consists of empirically investigating the annual changes in the ROAs of the nine listed South African Banking Groups over the period 2000 to 2008. The study consists of a two stage process. Data envelopment analysis (DEA) is conducted and resultant DEA scores are combined with the calculated ROAs of banks to provide efficiency adjusted ROA. The findings of this research paper shows that combining the CRS efficiency of bank groups with ROA provides a more reliable measure of future financial performance than just conventional ROA figures and efficiency figures.